Roles of Social Pain and Defense Mechanisms in Response to Social Exclusion Reply to Panksepp (2005) and Corr (2005). (article). - MacDonald, Geoff
In comments of G. MacDonald and M. R. Leary (2005), J. Panksepp (2005) argued for more emphasis on social pain mechanisms, whereas P. J. Corr (2005) argued for on physical defense mechanisms. In response to the former, the authors clarify their positions on the topics of anger, the usefulness of rat models, the role of analgesic mechanism, and the basic motivational processes. In response to the latter, the authors clarify their positions on the topics of relation of social exclusion to fear, the value of the pain affect construct, and the nature of social pain experience. The authors conclude that consideration of the roles of both social pain and defense mechanisms is essential to best understand human response to social exclusion. -- [from the author).
Keywords: Psychology-Periodicals.